2018
DOI: 10.1016/j.neuroscience.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Alpha Oscillations and Attentional Control: A Virtual Reality Neurofeedback Study

Abstract: In press in Neuroscience: https://doi.org/10.1016/j.neuroscience.2017.06.007The content of this manuscript does not match the content of the published work.Two competing views about alpha oscillations suggest that cortical alpha reflect either cortical inactivity or cortical processing efficiency. We investigate the role of alpha oscillations in attentional control, as measured with a Stroop task. We use neurofeedback to train 22 participants to increase their level of alpha amplitude. Based on the conflict/co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 31 publications
0
60
4
Order By: Relevance
“…Although increased alpha has been linked to enhanced attentional focus and cognitive performance (e.g., Klimesch, 1999 ; Jensen et al, 2002 ; Cooper et al, 2003 ; Sauseng et al, 2005 ; Klimesch et al, 2007 ; Berger and Davelaar, 2018 ), here we found that learning to increase alpha is associated with an absence (or restriction) of an evaluative process that operates on the products of sensory and cognitive processes. Thus, a cortical area could be in a heightened state of attention to augment sensory or cognitive information, in the absence of emotive-evaluative processing.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Although increased alpha has been linked to enhanced attentional focus and cognitive performance (e.g., Klimesch, 1999 ; Jensen et al, 2002 ; Cooper et al, 2003 ; Sauseng et al, 2005 ; Klimesch et al, 2007 ; Berger and Davelaar, 2018 ), here we found that learning to increase alpha is associated with an absence (or restriction) of an evaluative process that operates on the products of sensory and cognitive processes. Thus, a cortical area could be in a heightened state of attention to augment sensory or cognitive information, in the absence of emotive-evaluative processing.…”
Section: Discussioncontrasting
confidence: 78%
“…In this study, we investigated the mental mindset of individuals who experienced a single 5-min NFT session to increase their alpha frequency over the frontal cortex, which has been shown to be related to improved cognitive control ( Ros et al, 2013 ; Berger and Davelaar, 2018 ). The short session allowed a large number of individuals to be classified as non-learners to which the smaller number of learners could be compared.…”
Section: Discussionmentioning
confidence: 99%
“…EEG has been employed in investigations of various cognitive variables in 3D virtual learning environments. Frontal alpha EEG was recorded in a study of its role in attentional control; the study also demonstrated the importance of the immersion and engagement afforded by a 3D virtual learning environment (Berger and Davelaar, 2018). In a study of the effect of competition, while shooters were immersed in a virtual environment representing a shooting range, changes in alpha oscillatory activity were found during aiming that were associated with better performance (Pereira et al, 2018).…”
Section: Related Workmentioning
confidence: 98%
“…Another comparative study of a 2D cinema screen (fixed viewpoint) and IVR reported better attentional control on Stroop tasks, which was associated with increased prefrontal alpha power. This improved performance was only observed in the consumer-friendly HMD (Oculus Rift)-based neurofeedback training group (Berger & Davelaar, 2018). However, the authors used different visual stimuli in the neurofeedback training tasks, such as a 3D vase in the IVR, but a 2D square on the cinema screen.…”
Section: Introductionmentioning
confidence: 99%